O desenvolvimento local a partir da inserção da atividade turística em Unidades de Conservação: estudo de caso da RPPN Ninho do Corvo, Prudentópolis - PR - Alberton, Vanessa (2016)
Among the various ways to develop community, tourism activities appear as tools that help in the local development. One of the possibilities of combining tourism and local development is through conducting tourism activities in protected areas, either through ecotourism, adventure tourism or other ways. This study was developed in the Private Natural Heritage Reserve (PNHR) Crow's Nest in the city of Prudentopolis, Parana State, and aimed to characterize the tourist resort PNHR Crow's Nest and actions for local development. Through qualitative and quantitative research and application interviews were addressed 24 persons directly or indirectly connected with the project. It is noteworthy that, after being acquired in 2002, the PNHR underwent an environmental restructuring process, since until then was used for planting and grain. Currently develop adventure tourism activities, focusing on eco-tourism and environmental education. Although in small proportions, the demand of existing tourism activities in the project studied assists in surrounding economic development by generating jobs and income. The PNHR contributes to social development, since it enables the realization of training courses, moments of interaction of employees with tourists and those with nature, learning new knowledge and sustainable actions by employees. It contributes to the environmental, smaller in size, since the protected area is small and the degradation that occurs in the vicinity just neutralizing the benefits generated by PNHR.